Interpretace základních problémů národních dějin v dílech čelných představitelů albánského národního hnutí - Křepinský, Matěj (Univerzita Karlova, Filozofická fakulta, 2020)
The thesis focuses on the shaping of the national history of Albanians during the Albanian national movement. The time frame of the study is epoch between 1854 when Johann Georg von Hahn published Albanian Studies, and 1912 remarking proclamation of Albanian independence. The main goal of the paper is to introduce the structure of Albanian historical narrative in its romantic phase. For this purpose, the content analysis of works of seven main representatives of the national movement was used. Selected authors include: Jeronim de Rada, Pashko Vasa, Thimi Mitko, Spiro Risto Dine, Sami Frashëri, Naim Frashëri, Jani Vreto. The thesis explains the timeline of historical narrative and the perspective on the role of religion and religious communities. The study also covers creating the pantheon of national heroes and perception of neighbouring nations. The construct of the historical narrative is described in the context of beginnings of European scientific research about Albanian history. A reader will also get familiar with elementary ideological development of the Albanian national movement on the background of pivotal historical moments. The attachment of the thesis represents short biographies of selected authors. Práce zkoumá utváření obrazu národních dějin Albánců během albánského národního hnutí. Zkoumané období je vymezeno rokem 1854, kdy Johann Georg von Hahn publikoval Albánská studia, a vyhlášením albánské nezávislosti roku 1912. Cílem práce je seznámit čtenáře se strukturou albánského historického narativu v jeho romantické fázi s použitím obsahové analýzy prací sedmi předních představitelů albánského národního hnutí: Jeronima de Rady, Pashka Vasy, Thimiho Mitka, Spira Rista Dineho, Samiho Frashëriho, Naima Frashëriho a Janiho Vreta. Vysvětlena je časová linie historického příběhu, pohled na roli náboženství a náboženských obcí. Práce dále popisuje utváření panteonu hrdinů albánských dějin a pohledu na sousední národy. Konstrukt historického narativu je zasazen do kontextu počátků vědeckého bádání o ...